Imagem corporal e suas dimensões em relação às condições sociodemográficas e práticas alimentares de adolescentes brasileiros: resultados da Pesquisa Nacional de Saúde do Escolar 2015 - Batista, Leticia Spricido [UNIFESP] (2020)
Every teenager is susceptible to social pressures in their development. These young people form opinions in relation to the perfect body and the more this body distances itself from the real, the greater the possibility of conflict, compromising their self- esteem. In search of the ideal body, some adolescents adopt unhealthy behaviors for health, such as excessive concern for weight control, decreased caloric intake, among others. These associations between body dissatisfaction and the adoption of unhealthy behaviors, result in compromised physical and psychological health, leading to a serious public health concern. The purpose of this dissertation is to analyze the dimensions of body image in adolescents in Brazil and its relationship with sociodemographic factors, food and nutritional status, according to the National School Health Survey. The research method used was based on data from the National School Health Survey carried out in 2015. The association between the frequency of responses was established using Pearson's chi-square test, and the analysis of associations occurred through the model of univariate and multiple Poisson regression. For the results, data from 16,556 students were analyzed, in which girls presented twice as many distortions with the image compared with boys. In all dimensional spheres of body image, there were distortions in appearance for both sexes. The formation of body image in all dimensions occurs due to several factors and is influenced by the school environment, the media, the support of family and friends and the values inserted in the individual's culture. Young people who are dissatisfied with their image and want a slimmer body decrease their consumption of foods considered unhealthy, but do not increase their consumption of sizable healthy foods, which may reflect a restriction in their diet. At the conclusion of this research, the findings highlight the importance of multidimensional interventions that also address psychological factors, specifically cognitive-behavioral approaches.